2017
DOI: 10.1021/jacs.7b07731
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Droplet Microreactor for Catalysis Reactions Not at Equilibrium

Abstract: We develop a novel strategy to more effectively and controllably process continuous enzymatic or homogeneous catalysis reactions based on nonaqueous Pickering emulsions. A key element of this strategy is "bottom-up" construction of a macroscale continuous flow reaction system through packing catalyst-containing micron-sized ionic liquid (IL) droplet in oil in a column reactor. Due to the continuous influx of reactants into the droplet microreactors and the continuous release of products from the droplet micror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
98
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 60 publications
(104 reference statements)
0
98
0
2
Order By: Relevance
“…Pickering emulsions, a type of emulsion that are stabilized by colloidal particles, have attracted tremendous interest for biphasic enzyme catalysis . Compared to conventional surfactant‐stabilized emulsions, Pickering emulsions offer many unique advantages, such as enhanced enzyme stability, simplified product separation, and facile enzyme recycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pickering emulsions, a type of emulsion that are stabilized by colloidal particles, have attracted tremendous interest for biphasic enzyme catalysis . Compared to conventional surfactant‐stabilized emulsions, Pickering emulsions offer many unique advantages, such as enhanced enzyme stability, simplified product separation, and facile enzyme recycling.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Pickering emulsions, at ype of emulsion that are stabilized by colloidal particles, have attracted tremendousi nterest for biphasic enzymec atalysis. [9][10][11][12][13][14][15][16][17] Compared to conventional surfactant-stabilized emulsions, Pickering emulsions offer many unique advantages,s uch as enhanced enzyme stability, simplified product separation, and facile enzyme recycling. Pioneering work on the immobilization of enzymesb yu sing Pickering emulsions was accomplished by the groups of Wang and van Hest, who used hydrophobic SiO 2 nanoparticles and polymersomes, respectively,t oe mulsify aqueous solutionso fe nzymes in organic medium.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] They have been widely used as catalysts for a large number of organic transformations. [30][31][32][33][34][35][36][37][38][39] However, their application as catalysts for the synthesis of 2-arylbenzoxazole, 2-arylbenzimidazoles, and 2-arylbenzothiazoles via the condensation of aldehydes with o-aminophenols, o-phenylenediamine, and o-aminothiophenols, respectively, has not been known in the literature. In the continuation of our study in ionic liquids application, we reported herein the use of phosphonium acidic ionic liquid as a green and efficient catalyst for the synthesis of the above mentioned arylated heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, noninterference cannot always be avoided and catalystnon-compatibility in fact offers another main challenge for efficient tandem catalysis, for example when combining antagonistic catalysts such as an acid andabase. [18][19][20][21][22] For example, Resasco and coworkers reported on phase-selective catalysis using carbon nanotube-silica nanohybrids stabilized PEs in catalytic hydrogenationr eactions [23,24] andt he catalytic upgrading of biofuels by using hydrophobic zeolites acting as PE stabilizers. Various approaches have been taken towards the design of bifunctional acid-base catalysts, often relying on the spatial separation of the reactive entities on polymeric or oxidic support materials, [5,6] for example, in the form of yolk-shellm aterials, [7] metal-organic frameworks (MOFs), [8][9][10][11] shell cross-linked micelles, [12,13] or star polymers.…”
mentioning
confidence: 99%
“…[18][19][20][21][22] For example, Resasco and coworkers reported on phase-selective catalysis using carbon nanotube-silica nanohybrids stabilized PEs in catalytic hydrogenationr eactions [23,24] andt he catalytic upgrading of biofuels by using hydrophobic zeolites acting as PE stabilizers. [18][19][20][21][22] For example, Resasco and coworkers reported on phase-selective catalysis using carbon nanotube-silica nanohybrids stabilized PEs in catalytic hydrogenationr eactions [23,24] andt he catalytic upgrading of biofuels by using hydrophobic zeolites acting as PE stabilizers.…”
mentioning
confidence: 99%